Treponema species enrich the gut microbiota of traditional rural populations but are absent from urban individuals. (January 2019) - Angelakis, E.; Bachar, D.; Yasir, M.; Musso, D.; Djossou, F.; Gaborit, B.; Brah, S.; Diallo, A.; Ndombe, G.M.; Mediannikov, O.; Robert, C.; Azhar, E.I.; et al.
Abstract: There is a significant gap in our knowledge of the microbe–host relationship between urban and traditional rural populations. We conducted a large-scale study to examine the gut microbiota of different traditional rural and urban lifestyles in human populations. Using high-throughput 16S ribosomal RNA gene amplicon sequencing, we tested urban French, Saudi, Senegalese, Nigerian and Polynesian individuals as well as individuals living in traditional rural societies, including Amazonians from French Guiana, Congolese Pygmies, Saudi Bedouins and Algerian Tuaregs. The gut microbiota from individuals living in traditional rural settings clustered differently and presented significantly higher diversity than those of urban populations (p 0.01). The bacterial taxa identified by class analysis as contributing most significantly to each cluster were Phascolarctobacterium for traditional rural individuals and Bifidobacterium for urban individuals. Spirochaetae were only present in the gut microbiota of individuals from traditional rural societies, and the gut microbiota of all traditional rural populations was enriched with Treponema succinifaciens . Cross-transmission of Treponema from termites or swine to humans or the increased use of antibiotics in nontraditional populations may explain why Treponema is present only in the gut microbiota of traditional rural populations.